Self-Efficacy of the Elementary School Pre-Service Teacher Students in Science Learning - Syafrilianto, Syafrilianto; Afriandi, Muhammad; Lufri, Lufri; Andromeda, Andromeda; Mufit, Fatni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aimed to examine the self-efficacy profile of pre-service teachers from the Islamic Elementary School Teacher Education Program at Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary in Padangsidimpuan, specifically focusing on their science teaching self-efficacy. Using a descriptive quantitative research design with a survey method, the study utilized a 26-item self-efficacy questionnaire. The data were analyzed descriptively, calculating the average percentage of students who demonstrated self-efficacy for each criterion within the corresponding indicators. The research involved 180 out of 207 fifth-semester students enrolled in the 2024/2025 academic year. A Google Form survey, structured according to the Science Teaching Self-Efficacy Belief Instrument (STEBI), assessed two key indicators: Science Teaching Outcome Expectancy (STOE) and Personal Science Teaching Efficacy (PSTE). Modifications were made to align the indicators with the specific context and characteristics of the participants. Additionally, a small group of respondents was interviewed. Findings revealed that 14.2% of students strongly agreed with the PSTE criterion, while 54.9% agreed. For STOE, 20.7% strongly agreed, and 51.1% agreed. When combining both indicators, 68.9% of students exhibited a high level of self-efficacy in PSTE, and 71.8% in STOE. Overall, the majority of aspiring MI/SD teachers demonstrated high self-efficacy in their science teaching abilities.Keywords: MI/SD pre-service teacher students; self-efficacy; science learning